Expanding the Molecular Spectrum of Secretory Carcinoma of Salivary Glands With a Novel VIM-RET Fusion - Skálová, Alena; Banečkova, Martina; Thompson, Lester D R; Ptáková, Nikola; Stevens, Todd M; Brcic, Luka; Hyrcza, Martin; Michal, Michael; Simpson, Roderick H W; Santana, Thalita; Michal, Michal; Vaněček, Tomas; et al. (The American journal of surgical pathology, 2020)
BACKGROUND: Secretory carcinoma (SC), originally described as mammary analogue SC, is a predominantly low-grade salivary gland neoplasm characterized by a recurrent t(12;15)(p13;q25) translocation, resulting in ETV6-NTRK3 gene fusion. Recently, alternative ETV6-RET, ETV6-MAML3, and ETV6-MET fusions have been found in a subset of SCs lacking the classic ETV6-NTRK3 fusion transcript, but still harboring ETV6 gene rearrangements. DESIGN: Forty-nine cases of SC revealing typical histomorphology and immunoprofile were analyzed by next-generation sequencing using the FusionPlex Solid Tumor kit (ArcherDX). All 49 cases of SC were also tested for ETV6, RET, and NTRK3 break by fluorescence in situ hybridization and for the common ETV6-NTRK3 fusions using reverse transcription polymerase chain reaction. RESULTS: Of the 49 cases studied, 37 (76%) occurred in the parotid gland, 7 (14%) in the submandibular gland, 2 (4%) in the minor salivary glands, and 1 (2%) each in the nasal mucosa, facial skin, and thyroid gland. SCs were diagnosed more frequently in males (27/49 cases; 55%). Patients' age at diagnosis varied from 15 to 80 years, with a mean age of 49.9 years. By molecular analysis, 40 cases (82%) presented the classic ETV6-NTRK3 fusion, whereas 9 cases (18%) revealed an alternate fusion. Of the 9 cases negative for the ETV6-NTRK3 fusion, 8 cases presented with ETV6-RET fusion. In the 1 remaining case in the parotid gland, next-generation sequencing analysis identified a novel VIM-RET fusion transcript. In addition, the analysis indicated that 1 recurrent high-grade case in the submandibular gland was positive for both ETV6-NTRK3 and MYB-SMR3B fusion transcripts. CONCLUSIONS: A novel finding in our study was the discovery of a VIM-RET fusion in 1 patient with SC of the parotid gland who could possibly benefit from RET-targeted therapy. In addition, 1 recurrent high-grade case was shown to harbor 2 different fusions, namely, ETV6-NTRK3 and MYB-SMR3B. The expanded molecular spectrum provides a novel insight into SC oncogenesis and carries important implications for molecular diagnostics, as this is the first SC-associated translocation with a non-ETV6 5' fusion partner. This finding further expands the definition of SC while carrying implications for selecting the appropriate targeted therapy.
Keywords: Proto-Oncogene Proteins c-ret; dospělí; Proto-Oncogene Proteins c-myb; Mammary Analogue Secretory Carcinoma; Female; Salivary Gland Neoplasms; Adult; mladý dospělý; ženské pohlaví; protoonkogenní proteiny c-myb; fúzní onkogenní proteiny; Adolescent; lidé; vimentin; onkogenní fúze; Vimentin; Oncogene Proteins, Fusion; Salivary Proteins and Peptides; sekreční karcinom mamárního typu; nádory slinných žláz; protoonkogenní proteiny c-ret; Male; Aged; Young Adult; Oncogene Fusion; lidé středního věku; senioři; mužské pohlaví; slinné proteiny a peptidy; Middle Aged; mladiství; Humans